2004
DOI: 10.1901/jaba.2004.37-89
|View full text |Cite
|
Sign up to set email alerts
|

Training Educators to Implement Functional Analyses

Abstract: The present study examined the use of an instructional workshop for training educators to conduct functional analyses. Results indicated that 2 of 3 participants met the accuracy criterion following group training, whereas 1 participant required direct verbal feedback. During generalization probes, one participant accurately conducted sessions with a student in her classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 3 publications
5
66
1
6
Order By: Relevance
“…However, most of the participants in the Neef et al investigation also required live modeling and feedback in addition to video training in order to master the target skills. A number of other investigations have included video as one component of training programs, but effects of the video relative to other training procedures were not specifically evaluated (e.g., Buzhardt & Heitzman-Powell, 2005;Cooper & Browder, 2001;Kuhn, Lerman, & Vorndran, 2003;McCartney, Anderson, & English, 2005;Wallace, Doney, Mintz-Resudek, & Tarbox, 2004). To date, video as a distinct training procedure has not received research emphasis as a means of helping train staff to implement individualized intervention plans for people with challenging behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the participants in the Neef et al investigation also required live modeling and feedback in addition to video training in order to master the target skills. A number of other investigations have included video as one component of training programs, but effects of the video relative to other training procedures were not specifically evaluated (e.g., Buzhardt & Heitzman-Powell, 2005;Cooper & Browder, 2001;Kuhn, Lerman, & Vorndran, 2003;McCartney, Anderson, & English, 2005;Wallace, Doney, Mintz-Resudek, & Tarbox, 2004). To date, video as a distinct training procedure has not received research emphasis as a means of helping train staff to implement individualized intervention plans for people with challenging behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have assessed skills in both simulated (Moore et al, 2002;Wallace, Doney, Mintz-Resudek, & Tarbox, 2004) and natural settings (Erbas, Tekin-Iftar, & Yucesoy, 2006), respectively. Phillips and Mudford (2008) demonstrated that residential caregivers could be taught to conduct FA sessions when assessing client's behavior in clinical settings.…”
mentioning
confidence: 99%
“…Master's or doctoral level behavior analysts oversaw the implementation of this analysis at all times. Therefore, when given the proper training, it may be possible for individuals with a limited background in behavior analysis and functional analysis methodology to conduct the MFA (e.g., Wallace, Doney, Mintz-Resudek, & Tarbox, 2004).…”
Section: Discussion and Recommendations For Practitionersmentioning
confidence: 99%